Enhanced Antibacterial Efficacy of Bioceramic Implants Functionalized with Ciprofloxacin: An In Silico and In Vitro Study - Renata-Maria Văruț; Luciana Teodora Rotaru; Diana Cimpoesu; Mihaela Corlade; Cristina Elena Singer; Alin Iulian Silviu Popescu; Cristina Popescu; Iliescu Iulian-Nicolae; Adriana Mocanu; Mihaela Popescu; Mihai Alexandru Butoi; Oana Elena Nicolaescu (MDPI AG, 2024)
This study explores the antibacterial efficacy and cytotoxicity of ciprofloxacin-functionalized bioceramic implants. We synthesized hydroxyapatite-ciprofloxacin (HACPXCS) composites and applied them to titanium substrates (Ti-HA-CPX), evaluating their performance in vitro against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922). Antibacterial activity was assessed using the Kirby-Bauer disc diffusion method, while cytotoxicity was tested using mesenchymal stem cells. The results demonstrated that Ti-HA-CPX exhibited superior antibacterial activity, with inhibition zones of 33.5 mm (MIC 0.5 µg/mL) for Staphylococcus aureus (ATCC 25923) and 27.5 mm (MIC 0.25 µg/mL) for Escherichia coli (ATCC 25922). However, Ti-HA-CPX showed moderate cytotoxicity (80% cell viability). HACPXCS composites, whether chemically synthesized or mechanically mixed (HACPXMM), also displayed significant antibacterial activity, but with cytotoxicity ranging from low to moderate levels. Molecular docking studies confirmed strong binding affinities between ciprofloxacin and bacterial proteins, correlating with enhanced antibacterial efficacy. These findings suggest that Ti-HA-CPX composites offer a promising approach for single-stage surgical interventions in treating chronic osteomyelitis and infected fractures, balancing antibacterial effectiveness with manageable cytotoxicity.